Stochastic Growth Logistic Model with Aftereffect for Batch Fermentation Process - Norhayati, Rosli; Tawfiqullah, Ayoubi; Arifah, Bahar; Haliza, Abdul Rahman; Madihah, Md Salleh (2014)

(untitled)
In this paper, the stochastic growth logistic model with aftereffect for the cell growth of C. acetobutylicum P262 and Luedeking-Piret equations for solvent production in batch fermentation system is introduced. The parameters values of the mathematical models are estimated via Levenberg-Marquardt optimization method of non-linear least squares. We apply Milstein scheme for solving the stochastic models numerically. The efficiency of mathematical models is measured by comparing the simulated result and the experimental data of the microbial growth and solvent production in batch system. Low values of Root Mean-Square Error (RMSE) of stochastic models with aftereffect indicate good fits.